2006
DOI: 10.1017/s1461145706006572
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age affect NK1 receptors in the human brain – a positron emission tomography study with [18F]SPA-RQ

Abstract: Substance P (SP) is a neurotransmitter and neuromodulator that mediates its effects in the brain predominantly via the neurokinin-1 receptors (NK1Rs). NK1Rs and SP have been shown clinically to be involved in nausea and emesis after chemotherapy (CINV) and have been implicated preclinically in a range of neuropsychiatric disorders but unlike CINV their blockade in these conditions does not have proven clinical value. We investigated whether age and gender affects NK1R binding potential (NK1R-BP; an index of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 75 publications
(89 reference statements)
2
21
0
1
Order By: Relevance
“…In addition, the full-length NK1R mRNA expression levels in the putamen was significantly higher than that in the cerebellum (P= 0.025). Considering that the binding affinity of the full-length NK1R to SP, its preferred agonist, is much higher (at least 10 fold) than that of the truncated NK1R (Fong et al, 1992), our data is in agreement with a recent report (Nyman et al, 2007) which demonstrated that putamen had the highest binding potential in the living human brain using PET and [ 18 F]SPA-RQ, a highly specific NK1R antagonist. Although the existence and expression of both the full-length and truncated NK1R have been documented, the differences in their expression in human brain tissue have been investigated only to a limited extent.…”
Section: Quantitation Of Full-length and Truncated Nk1r From Differensupporting
confidence: 92%
“…In addition, the full-length NK1R mRNA expression levels in the putamen was significantly higher than that in the cerebellum (P= 0.025). Considering that the binding affinity of the full-length NK1R to SP, its preferred agonist, is much higher (at least 10 fold) than that of the truncated NK1R (Fong et al, 1992), our data is in agreement with a recent report (Nyman et al, 2007) which demonstrated that putamen had the highest binding potential in the living human brain using PET and [ 18 F]SPA-RQ, a highly specific NK1R antagonist. Although the existence and expression of both the full-length and truncated NK1R have been documented, the differences in their expression in human brain tissue have been investigated only to a limited extent.…”
Section: Quantitation Of Full-length and Truncated Nk1r From Differensupporting
confidence: 92%
“…Positron emission tomography (PET) studies indicate that sex influences brain expression of dopamine (129, 130), serotonin (131), neurokinin 1 (132, 133), and opioids (134). Autoradiography studies in rodents further indicate sex differences in AMPA, kainate, and NMDA (135) as well as noradrenergic transmission (136).…”
Section: Hypothalamic Role In Hormonal Regulation Of Brain Dysmetria mentioning
confidence: 99%
“…NK-1R availability was quantified with the radioligand [ 18 F]SPA-RQ, a high-affinity NK-1R antagonist [29,58,73]. Images were acquired using a Siemens ECAT EXACT HR+ scanner (Siemens Healthcare Solutions, Deerfield, IL, USA: in-plane resolution full-width at half-maximum [FWHM] = 4.6 mm, axial FWHM = 3.5 mm, axial field of view = 15.52 cm) in 3-dimensional (3D) mode.…”
Section: Methodsmentioning
confidence: 99%